Pembobotan Kriteria Evaluasi Kinerja Pemasok dengan Mempertimbangkan Risiko Gangguan Menggunakan Metode Best Worst Method - Wahyu Elanda, Redian; Simbolon, Oky; Laymina Ikhsan, Wakhid (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
At PT X, an electronics manufacturer, disruptions caused by natural disasters and social factors have generated additional costs of about 8–10%. This condition underlines the importance of explicitly incorporating risk, especially disruption risk, into supplier evaluation. This study develops and weights supplier evaluation criteria by adding a risk dimension to the traditional dimensions of cost, quality, delivery, and flexibility. The Best Worst Method (BWM) is used to determine criteria weights through pairwise comparisons between the best and worst criteria, requiring fewer comparisons and improving the consistency of expert judgments. Data were obtained from three experienced procurement experts at PT X. The results show that cost and quality are the most influential dimensions, followed by delivery, risk, and flexibility. At the criteria level, product price, product reliability, on-time delivery, and risk-related indicators such as manufacturing capability, problem-solving capability, disaster recovery planning, performance history, and geographical location are relatively dominant. Low consistency values (ξ) indicate acceptable expert consistency. The resulting framework helps firms evaluate suppliers more comprehensively, reduce disruption-related costs, and enhance supply chain reliability.